2021
DOI: 10.35509/01239015.706
|View full text |Cite
|
Sign up to set email alerts
|

Características de los pacientes con cáncer de pulmón de célula no pequeña en el Instituto Nacional de Cancerología de Bogotá

Abstract: Objetivos: El objetivo fue describir las características demográficas, histopatológicas, biología molecular tumoral y estadificación de los pacientes con cáncer de pulmón de célula no pequeña atendidos entre diciembre de 2013 y diciembre  2018 en el Instituto Nacional de Cancerología. Métodos: Estudio descriptivo de corte transversal Resultados: Se incluyeron 392 pacientes con cáncer de pulmón de célula no pequeña, la mediana de edad fue 65.9 años (rango, 28,9 a 88,9 años). 198(50,5%) pacientes fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…In Colombia, lung cancer ranked fifth in incidence in 2020, following breast, prostate, colorectal, and stomach cancer. In terms of mortality, lung cancer is the second leading cause of cancer-related death in Colombia, with approximately 9.2 deaths per 100,000 population each year [ 16 , 17 ]. Adenocarcinoma is the most common histological variant in lung cancer patients in Colombia, followed by squamous cell carcinoma.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…In Colombia, lung cancer ranked fifth in incidence in 2020, following breast, prostate, colorectal, and stomach cancer. In terms of mortality, lung cancer is the second leading cause of cancer-related death in Colombia, with approximately 9.2 deaths per 100,000 population each year [ 16 , 17 ]. Adenocarcinoma is the most common histological variant in lung cancer patients in Colombia, followed by squamous cell carcinoma.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…The distribution by histopathology subtypes was led by adenocarcinoma (80% of patients). 24 The selection of systemic therapy depends on the molecular characteristics of the tumor (Fig. 4).…”
Section: Systemic Therapymentioning
confidence: 99%
“…Data in the local cohort revealed that patients with ALK rearrangement, EGFR mutation, or PD-L1 expression greater than or equal to 50% have better overall survival than patients without these features. 24 In the nonmutant driver population (EGFR wild type, ALK, ROS1 negative), CT combined with immunotherapy (IO) was the most frequent systemic therapy administered. 4 The most common cytotoxic agents used were carboplatin, pemetrexed, paclitaxel, and cisplatin.…”
Section: Systemic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…En general, el 54% tenía antecedente de exposición al tabaco y el 40% no los refirió. En este subgrupo, el 86% tuvo adenocarcinomas (ACPs) y la mayoría fueron mujeres (≈65%) (1). Estos datos son consistentes con diversos estudios que han revelado que el CP en personas nunca fumadoras representa entre el 25 y 40% (2).…”
unclassified